Pengaruh Pengalaman Praktik Kerja Lapangan, Motivasi Memasuki Dunia Kerja, dan Employability Skills Terhadap Kesiapan Kerja Siswa Kelas XII MPLB SMKN 1 Karanganyar - Rani Septiana (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of field work experience (PKL), motivation to enter the workforce, and employability skills on the work readiness of class XII MPLB students at SMKN 1 Karanganyar. The research method used was quantitative with data collection techniques through questionnaires and document analysis. The research sample consisted of 70 students selected using saturated sampling. Data were analyzed using multiple linear regression with the help of SPSS Statistics 17. The results showed that the three independent variables had a positive and significant effect on work readiness, both partially and simultaneously. The highest contribution was given by motivation to enter the workforce (33.6%), followed by employability skills (12.3%) and PKL experience (6.3%). Overall, the three variables contributed 52.2% to students' work readiness. These findings imply the importance of improving the quality of PKL, strengthening student motivation, and developing employability skills in the vocational school curriculum.